Peningkatan Produktivitas Kerja Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Melalui Perbaikan Lingkungan Kerja - Muzakir Muzakir (Jurnal Optimalisasi, 2016)
The work environment is an important part of the company, because the work environment has a direct impact on work productivity of employees. Appropriate environment can give the impression of comfort and serves as a means to be aware of the effectiveness and efficiency of work whereas good working environment can result in health problems and accidents at production units which in turn would lower the overall productivity of the company. Objective is to determine how much influence the work environment, especially exposure to heat due to the temperature of the stove is too high on employee productivity in making karah cakes and determine what factors are likely to influence the work environment on employee productivity in the manufacture of karah baking. Stages of research from the discovery of symptoms, to formulate the problem, to know the powerful factor influencing the occurrence of the problem. This research was conducted by taking samples at UMKM karah cakes maker with variable gauge how the work environment influence on the productivity of UMKM karah cakes maker.Keyword: Productivity, Work Environment, UMKM.